Analysis of the confluence between Nigeria’s development strategies and its agricultural public expenditures - Mogues, Tewodaj; Olofinbiyi, Tolulope (African Journal of Food, Agriculture, Nutrition and Development, 2018)
This paper seeks to understand the features of public spending in the agricultural sector within the context of Nigeria’s federal structure and decentralized system. Specifically, the study aims to examine the extent to which the level and composition of public spending in the agricultural sector is consistent with both national and subnational priorities. The study also analyzed the efficiency of public resource allocation to agriculture in line with stated priorities at the federal and subnational levels. It provides analysis of public expenditures at the federal and state levels, the latter drawing from three case study states: Cross River, Niger, and Ondo states. The main period covered in this study are three important policy regimes: the era of NEEDS (National Economic Empowerment and Development Strategy) during the administration of President Olusegun Obasanjo, the seven-point agenda era of President Umaru Musa Yar’Adua, and the era of Vision 20:2020 of President Goodluck Jonathan. Although considerable efforts have been made to identify development priorities and articulate policies and strategies for improved performance of the agricultural sector, no sharp connection has been made with the expenditure policy. At the federal level, the situation was beginning to improve in the aftermath of the articulation of the Agricultural Transformation Agenda (ATA) and alignment of expenditures toward the attainment of targets set in various strategic components of the agenda. At the subnational level, expenditure decisions do not follow a results-based framework, and there is no analytical basis for a logical assessment of expenditure impact. The defective linkage between expenditure decisions and prioritization of projects manifests in the study states, in particular where some activities that were not budgeted for ended up being funded whereas those already budgeted for receive no funding at all. Future research should conduct political economy analysis to shed light on circumstances that lead to a disconnect, and what factors lead to a stronger relationship between the design of strategies and actual public expenditures undertaken.